Neutrino mass in higgs triplet model / Ong Jian Fuh - Ong, Jian Fuh (2012)
We study the νe − e annihilation from low to ultrahigh energy in the frame- work of Higgs Triplet Model (HTM). We add the contribution of charged Higgs boson exchange to the total cross section of the scattering. We obtain the upper bound hee/MH± . 2.8 × 10−3GeV −1 in this process from low energy experiment. We show that by using the upper bound we obtained, the charged Higgs contribution could give enhancements to the total cross section with respect to the SM prediction at s ≈ M2H ±. Furthermore, at the energy above theWpole, we compareW−H1,W+H−−, H+H−−, H2H− and W−Z0 production. We compare the total cross section of νe − e and W−Z0 at resonance energy , in which a charged Higgs boson is exchanged. We discuss the possibilities of the Higgs search through the products of Higgs bosons decay at large Higgs lepton coupling constant.